The Value of the University Armed Service Units - Woodward, Rachel (Ubiquity Press, 2015)
This book provides a comprehensive assessment of the value of the university armed service units - the University Officer Training Corps, University Royal Naval Units and University Air Squadrons. The units, many of which date back to the early 20th century, exist in order to provide students at UK universities with an experience of the British armed forces. Participation in the units is entirely voluntary, and there is no expectation that students will go on to join the armed forces on graduation, although a proportion of students each year do so.The Value of the University Armed Service Units brings together the results of a research project which explored what the value of the units might be to student participants, to graduates in civilian jobs who had the experience as students, to the armed forces, to universities whose students take part in the units, and to employers of graduates with service unit experience. This book draws on quantitative and qualitative research data to explore whether, how, and why the units have value to these different groups. Significant conclusions include the extent to which the units are able to assist students with the development of their transferable (graduate) skills; the potential significance of the units for future recruitment to the armed forces, particularly the Reserves; and the effect of unit experience in developing an informed understanding of the role and function of the British armed forces amongst the wider civilian population.